Synergetic mechanism of agricultural logistics ecosphere –the case study based on Jiangxi Taoxin - Hu, Yi; Shu, Hui (Nankai business review international, 2023)
Purpose As the saying goes, “food is heaven of people” the development of agriculture is not only related to the quality of human life but also profoundly affects the efficiency of economic operation. However, under the background of rapid economic and technological development, China’s agricultural modernization process is very slow and incompatible with the development trend of economic modernization. Therefore, it is particularly necessary to innovate the traditional agricultural development model to break through the bottlenecks encountered in the transformation process of agricultural modernization. The proposal of the agricultural logistics ecosphere is to solve the problems of poor industrial linkage, low technical level and backward operation mode in the development process of traditional agriculture, and it is an important starting point for agricultural supply-side structural reform. This study aims to answer three questions in three aspects, namely, what is the agricultural logistics ecosphere, analyzes the general composition of the agricultural logistics ecosphere and how the subjects of the agricultural logistics ecosphere cooperate. It also puts forward suggestions for the coordinated development of the agricultural logistics ecosphere under the leadership of Taoxin. Also, it inspires the transformation of the agricultural development model in other regions and countries. Design/methodology/approach This study adopts a case study and a qualitative analysis method to collate the first-hand and secondary data obtained from the interview and form a tertiary coding. It explores the mechanism of coordinated development of the agricultural logistics ecosphere from four levels: goal synergy, resource synergy, ability synergy and benefit synergy. Findings First, the formation of the agricultural logistics ecosphere will not be achieved overnight, as operational management matures and ecosphere experiences the germination-development-mature evolution process. Second, target synergy is the foundation and premise for the formation of agricultural logistics ecosphere: to attract external resources with Taoxin characteristic core resources, to attract external resources to achieve synergy, to provide a guarantee for the realization of the maximum value of the agricultural logistics ecosphere and then to realize the interest synergy of internal and external subjects. Third, driving agricultural products upward in the “10 + 1” model: it is the core resource of the agricultural logistics ecosphere led by Taoxin and attracts external subjects to gather with core resources to further improve the value of the ecosphere. The improvement of the value of the ecosphere can broaden the ecosphere network. This is both an important construction of the ecosphere, and it is also the path choice of the coordinated development of the agricultural logistics ecosphere. Originality/value This study has a very important practical value and theoretical significance. In practical terms, the integration of “primary, secondary and tertiary industries” is helpful to foster new momentum for the development of agriculture and rural areas and promote the general framework of the agricultural logistics economy, the analysis of the general mechanism and extension of the transition of the new economy.